Dancing on My Own: Parasocial Love, Romantic Loneliness, and Imagined Interaction. (June 2022) - Hu, Mu; Zhang, Bingqing; Shen, Yinghe; Guo, Jing; Wang, Shuwen
The present study examined the relationships between people's romantic loneliness, parasocial love (PSL), and imagined interaction (II) with media figures they viewed as romantic partners. Two hundred and twenty four college students in a Chinese university participated in the survey study. Romantic loneliness was negatively related to PSL moderated by gender. The negative relationship only emerged in males but not in females. People who had II with the personae had stronger PSL in contrast those who didn't. PSL was positively related to II's attributes of frequency and valence and functions of compensation and relationship maintenance. Frequency of II negatively mediated the relationship between romantic loneliness and PSL.